Determining the Viability of Orchid seeds using the Tetrazolio and Carmín Índigo Tests (2015)
Orchid species are endangered worldwide due to human intervention. Therefore, it is necessary to analyze the germination capacity (viability) of orchids' seeds as essencial step for its conservation. This research determined the viability of the seeds species of orchids Elleanthus arauntiacum, Epidendrum sp, Maxillaria sp, Odontoglossum lindenii, Prosthechea sp, Telipogon dubios, Stelis sp, Elleanthus sp, Epidendrum elongatum y Cyrtochilum sp, using the Tetrazolium and Indigo carmin tests. Several f eld trips to the province of El Escorial in Norte de Santander, Colombia were done for collection of mature capsules of the different species of orchids. Then, was the seeds' viability by using the tetrazolium and Indigo Carmine tests. Subsequently, the data obtained from the two tests was evaluated. The correlation coeff cient between the Tetrazolium and Indigo Carmine tests was 0.419, indicating a weak relationship between the two trials with statistically signif cant differences P:0.05. It was found that the tetrazolium test was the most eff cient to determine the viability of orchid seeds being studied.